2013
DOI: 10.1074/jbc.m112.435750
|View full text |Cite
|
Sign up to set email alerts
|

NMR Reveals Double Occupancy of Quinone-type Ligands in the Catalytic Quinone Binding Site of the Na+-translocating NADH:Quinone Oxidoreductase from Vibrio cholerae

Abstract: Background:The Na ϩ -NQR is a respiratory Na ϩ pump found in prokaryotes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 38 publications
(43 reference statements)
0
17
2
Order By: Relevance
“…With Na + -NQR solubilized in lauryl-dimethyl-amine N-oxide, Q8 was lost from the enzyme Casutt et al, 2011). We recently showed that the quinone-binding site in NqrA could accommodate two quinone molecules in close proximity (Nedielkov et al, 2013). With eight isoprenoid units, Q8 is a very hydrophobic molecule, but its redox-reactive quinone head group is rather hydrophilic.…”
Section: Molecular Architecture Of Na + -Nqrmentioning
confidence: 99%
“…With Na + -NQR solubilized in lauryl-dimethyl-amine N-oxide, Q8 was lost from the enzyme Casutt et al, 2011). We recently showed that the quinone-binding site in NqrA could accommodate two quinone molecules in close proximity (Nedielkov et al, 2013). With eight isoprenoid units, Q8 is a very hydrophobic molecule, but its redox-reactive quinone head group is rather hydrophilic.…”
Section: Molecular Architecture Of Na + -Nqrmentioning
confidence: 99%
“…For instance, the spatial distances between several pairs of redox cofactors in the proposed electron transfer pathway are too large to support physiological rates of electron transfer; for example, the edge-toedge distance between the [2Fe-2S] cluster in NqrF and the Fe(Cys) 4 in NqrD (33.4 Å) and between the FMN and the riboflavin cofactor in NqrB (29.3 Å). The fact that electron transfer between these cofactors takes place indicates that the subunits harboring the cofactors undergo large conformational changes during turnover that decrease these spatial gaps (13).Additionally, the crystallographic model lacks an anticipated tightly bound quinone, which has been reported in the enzyme preparations from different laboratories (4,6,8) and suggested to be located in NqrA on the basis of photoaffinity labeling and NMR studies (7,9). In the crystallographic model, the NqrA subunit includes a deep cavity that is large enough to accommodate a ubiquinone molecule, but the cavity is ϳ20 Å above the predicted membrane surface and the distance between the cavity and the riboflavin in NqrB subunit is too large (Ͼ40 Å) to be consistent with electron transfer during turnover (Fig.…”
mentioning
confidence: 99%
“…Additionally, the crystallographic model lacks an anticipated tightly bound quinone, which has been reported in the enzyme preparations from different laboratories (4,6,8) and suggested to be located in NqrA on the basis of photoaffinity labeling and NMR studies (7,9). In the crystallographic model, the NqrA subunit includes a deep cavity that is large enough to accommodate a ubiquinone molecule, but the cavity is ϳ20 Å above the predicted membrane surface and the distance between the cavity and the riboflavin in NqrB subunit is too large (Ͼ40 Å) to be consistent with electron transfer during turnover (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were harvested, washed once with 50 mM sodium phosphate (pH 8.0) and 0.5 M NaCl and stored at Ϫ80°C. Disruption of cells in a continuous lysis system (Emulsiflex C3 homogenizer; Avestin) and preparation of membranes were performed as described previously (28). The membranes were suspended in 50 mM sodium phosphate (pH 8.0) containing 0.3 M NaCl and 5% (wt/vol) glycerol to a final concentration of approximately 10 mg protein ml Ϫ1 as determined by the bicinchoninic acid assay (29).…”
Section: Strains and Plasmids Vibrio Cholerae O395n1 (17) And Its Vamentioning
confidence: 99%